Biological anthropology - Park, Michael Alan (McGraw-Hill, 2013)
"Contemporary biological anthropology is a dauntingly broad field. It studies humans in the same way that zoologists study their subject species--from a perspective that includes all aspects of the species' biology and that emphasizes the interrelationships among those aspects. In addition to encompassing the traditional topics of the human fossil record and human biological variation, bioanthropology includes primatology, modern technologies in molecular genetics, human demography, disease and medical issues, development of the individual, life histories, and such applications as forensic anthropology. Bioanthropology also appreciates that our cultural behavior is an integral part of our behavior as a species"-- Provided by publisher